2015
DOI: 10.3390/ijerph120708009
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Quality of Park Play Spaces between Two Cities with Diverse Income and Race/Ethnicity Composition: A Pilot Study

Abstract: This study investigated the differences in the quality of park play spaces between an affluent and a non-affluent community in a large US Southeastern metropolitan area. Two cities were purposefully selected to reflect differences in household income and race/ethnicity characteristics. Using the Playable Space Quality Assessment Tool (PSQAT), all parks (n = 11, with six in the affluent city, and five in the non-affluent city) in these two cities were evaluated. The data were analyzed across three aspects of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 42 publications
1
14
0
1
Order By: Relevance
“…However, sufficient natural areas may not be available to all the population groups in a city. Because of biophysical and landscape prerequisites, natural areas and the quality of these spaces are often unequally distributed between groups of different socioeconomic status, age, and ethno-racial characteristics [ 52 , 53 , 54 , 55 , 56 , 57 ]. There may also be differences in how various groups use natural areas.…”
Section: Introductionmentioning
confidence: 99%
“…However, sufficient natural areas may not be available to all the population groups in a city. Because of biophysical and landscape prerequisites, natural areas and the quality of these spaces are often unequally distributed between groups of different socioeconomic status, age, and ethno-racial characteristics [ 52 , 53 , 54 , 55 , 56 , 57 ]. There may also be differences in how various groups use natural areas.…”
Section: Introductionmentioning
confidence: 99%
“…The park quality is considering factor that contribute to park visitation. Quality was mostly assessed through park amenities and hazards (Vaughan et al, 2013;Rigolon & Flohr, 2014;Jenkins et al, 2015;Hughey et al, 2016). Vegetation as trees and woodlands has a natural capacity to absorb and remove air pollutants (Chaparro & Terradas, 2009;Escobedo & Nowak, 2009;Gomez-Baggethun et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Both the proximity and quantity metrics ignore the inner characteristics of urban parks, and likely, that UGS quality is among the attributes that continually attracts nearby residents to visit those parks. A comparative study in a large US metropolitan area found significant differences in quality (i.e., location, care and maintenance, and entertainment value) between groups with different household income characteristics [38]. The influence of park quality on park usage might vary by gender, and the groups of active or female users could be significantly affected [40].…”
Section: Systematic Map Of the Features Of Access Inequity Researchmentioning
confidence: 99%